2020
DOI: 10.3390/pathogens9110921
|View full text |Cite
|
Sign up to set email alerts
|

Intra Vitam Diagnosis of Neglected Gurltia paralysans Infections in Domestic Cats (Felis catus) by a Commercial Serology Test for Canine Angiostrongylosis and Insights into Clinical and Histopathological Findings—Four-Case Report

Abstract: Gurltia paralysans is a metastrongyloid nematode which belongs to the Angiostrongylidae family and presents tropism for veins of the subarachnoid space in vivo of domestic and wild felids causing a progressive and chronic clinical manifestation of paraparesis/paraplegia. The geographic distribution of G. paralysans includes rural and periurban areas of South America and was recently reported in Europe. To date, a definitive diagnosis of feline gurltiosis is still conducted by post-mortem examination of the spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 32 publications
2
22
1
Order By: Relevance
“…A cross-reactivity of G. paralysans and A. vasorum using a commercial serological test developed for the diagnosis of canine angiostrongylosis in domestic dogs has been recently evaluated for the use in domestic cats with gurltiosis. Preliminary results showed that the Angio Detect Test™ (IDEXX Laboratories), a rapid test designed to detect circulating antigen based on A. vasorum-specific antibodies, can be used as an effective test for cats displaying clinical signs of G. paralysans infection (Gómez et al 2020).…”
Section: Diagnosismentioning
confidence: 99%
“…A cross-reactivity of G. paralysans and A. vasorum using a commercial serological test developed for the diagnosis of canine angiostrongylosis in domestic dogs has been recently evaluated for the use in domestic cats with gurltiosis. Preliminary results showed that the Angio Detect Test™ (IDEXX Laboratories), a rapid test designed to detect circulating antigen based on A. vasorum-specific antibodies, can be used as an effective test for cats displaying clinical signs of G. paralysans infection (Gómez et al 2020).…”
Section: Diagnosismentioning
confidence: 99%
“…Microscopic findings include vascular myelitis and intralesional adult parasites, which principally locate at subarachnoid space in some segments of the spinal cord (third thoracic vertebra to third lumbar vertebrae and fourth lumbar vertebrae to third sacral vertebrae) [38,39]. The gurltiosis intra vitam diagnosis is highly challenging due to the lack of evidence in the excretion of G. paralysans eggs and larvae stages, neither in feces nor in other body secretions [42], because the environmental stages and parasite transmission route remain unknown. Veterinary clinicians should include exhaustive clinical examination in cats with typical hind limbs neurological signs and complementary tests to approach the diagnosis of this parasitosis.…”
Section: Clinical Signs and Diagnosticmentioning
confidence: 99%
“…They suggested a cross-reaction between Angiostrongylus vasorum and G. paralysans-specific antigens, which could be used as a new diagnostic tool for feline gurltiosis. Nevertheless, it is necessary to analyze the sensibility and specificity compared with the specific antigen for this parasite to validate the serological test result [42].…”
Section: Clinical Signs and Diagnosticmentioning
confidence: 99%
“…An important difficulty in investigating the occurrence of this parasite is the fact that the diagnostic stage is unknown and diagnosis to date is only achieved in post mortem examination. In their study, Gómez et al [14] evaluated a commercial serological test, designed for the diagnosis of canine angiostrongylosis due to Angiostrongylus vasorum, for an intra vitam diagnosis of G. paralysans infection in cats. According to the results, a cross-reaction between A. vasorum-specific antigens and G. paralysans offers the possibility of using this antigen test as a diagnostic method for feline gurltiosis in live domestic cats.…”
Section: New Insights In Classical and Lesser Studied Feline Parasitesmentioning
confidence: 99%
“…According to the results, a cross-reaction between A. vasorum-specific antigens and G. paralysans offers the possibility of using this antigen test as a diagnostic method for feline gurltiosis in live domestic cats. Furthermore, this study presents the clinical and histopathological findings of four cases of feline natural infections, providing important insights on this neglected and little-known feline parasite [14].…”
Section: New Insights In Classical and Lesser Studied Feline Parasitesmentioning
confidence: 99%